Rise in Sales of Multi Axle Trucks in India : Governmental Initiatives, Industrial Development, and Operator Preferences - Sarkar, Abhijit; Jha, Ajeya; Mukherjee, Diganta (Indian Journal of Marketing, 2018)
The research paper expressed two aspects that affect truck operators, on the one hand, it demonstrated the relationship between the sale of heavy trucks and road, infrastructural, and industrial development while, on the other hand, it also showed how the business performance of truck owners gets affected by government policies and personal perceptions. The paper, in quest of these two objectives, also established a time series model (ARIMA model) and three regression equations that clearly explained the relationship between the relevant dependent and independent variables.